2022
DOI: 10.31234/osf.io/a5kzq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding burnout among parents of children with complex care needs: A scoping review followed by a stakeholder consultation

Abstract: Objective: The concept of parental burnout has been proposed to be helpful for describing and understanding the impact of parenting children with complex care needs (CCN). The objective of this scoping review was to describe the aims, methods, and results of research on burnout among parents of children with CCN, along with a stakeholder consultation to investigate what stakeholders consider as important insights and gaps based on the findings.Methods: Following the Joanna Briggs Institute for Reviewers’ Manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The emotional exhaustion subscale (EES) consists of 13 items, [1][2][3]5,6,8,10,11,[13][14][15][16][17] while the personal achievement subscale (PAS) consists of eight items. 4,7,9,12,[18][19][20][21] In the Duygun and Sezgin's study, Cronbach's α was found to be 0.83 for the EES and 0.72 for the PAS. 11 A total score cannot be obtained for the MBI; therefore, the score for each subscale is calculated separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emotional exhaustion subscale (EES) consists of 13 items, [1][2][3]5,6,8,10,11,[13][14][15][16][17] while the personal achievement subscale (PAS) consists of eight items. 4,7,9,12,[18][19][20][21] In the Duygun and Sezgin's study, Cronbach's α was found to be 0.83 for the EES and 0.72 for the PAS. 11 A total score cannot be obtained for the MBI; therefore, the score for each subscale is calculated separately.…”
Section: Methodsmentioning
confidence: 99%
“…11 Parental burnout has been defined as "long-term exposure to parent-related risks that can have serious psychosocial effects." 12 Each parent has a different strategy to cope with burnout, one of which is psychological resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews regarding parents of individuals with disabilities and/or complex care needs have also been done. However, in these studies the focus is primarily on one or two specific parts of the psychological aspects, for example, burn out (Patty, 2020), anxiety and depression (Scherer et al, 2019), or coping and quality of life (Fairfax et al, 2019).…”
Section: Introductionmentioning
confidence: 99%